The Effect of Minimum Wages on Teenage Unemployment Rates - Moore, Thomas Gale (Journal of Political Economy, 1971)
The model developed has the unemployment rates of four classifications of teenagers and the unemployment rate of males twenty to twenty-five as a function of overall labor market conditions, the minimum wage as a proportion of average hourly earnings for nonfarm workers, and the coverage of the minimum wage. The model hypothesizes that changes in the minimum wage relative to average hourly earning have an increasing effect as employers gain more time to adjust; consequently a distributed lag is used to measure the impact of the minimum wage. As might be expected, the minimum wage most adversely affected nonwhite teenagers; females sixteen to nineteen were more adversely affected than males.